Amjad Saqib on human dignity and systemic oppression in Pakistan's landscape - Jahangir, Junaid (My University, 2026)
In their book Economy Studies, de Muijnck and Tieleman call for the decolonisation of economics. They express concerns that Euro-centric theories of economics textbooks often sideline topics of power, discrimination, racism, colonialism, exploitation, and unequal life chances. Thus, they argue for including minority and global South voices that address these topics. My review of Muhammad Amjad Saqib’s book is inspired by this call. Distinguished economist, Akmal Hussain draws from politics, economics, history, religion, and folk poetry to argue that rent seeking elite have extracted Pakistan’s resources and attributes this behaviour to the colonised mind of the elite. The solution is to decolonise this consciousness by reconnecting with a folk cultural tradition that resists injustice and nurtures universal human solidarity. This decolonisation is about shifting from an extractive economy to building human capabilities.
Keywords: decolonisation; economics; folk cultural tradition